Kohesivitas Keagamaan Jamaah Pengajian Majlis Ta’lim Asy-Syifaa Wal Mahmuudiyyah - Deden Sumpena (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2015)
The existence of recital communities in society is extremely important, where people can learn the religion of Islam as the foundation of knowledge to practice their religion properly and correctly, and to increase devotion to Allah. Besides being a relationship between the public media, the public can follow the teachings also get an explanation of religion, the problems encountered in life, and a variety of other religious motivation in the study. These has motivates people to involve in religious lectures.